Understanding the Development of Chinese EFL Student–Teachers’ Pedagogical Content Knowledge - Li, Shuo; Liu, Liyan; Jiang, Anne Li (Frontiers in Psychology, 2021)
Efforts to improve student-teacher education have recently focused on developing adequate Pedagogical Content Knowledge (PCK) as a critical element for effective preparation. Despite many initiatives implemented in teacher education programs, however, their effectiveness in developing student-teachers’ PCK and factors affecting the PCK development are under-researched and evidenced. Drawing upon theories about and research on PCK, this study examined whether a recently updated two-year teacher education program could develop student-teachers’ PCK effectively and explored what factors influencing the PCK development of student-teachers with different developmental trajectories. Forty English-as-foreign-language (EFL) student-teachers on the program were involved as participants. This study employed a longitudinal research design. Data were collected at four different stages along with the program through the content representation matrix, interviews with all the participants, and focus group interviews with four particularly sampled participants. Findings revealed that the current teacher education program successfully enhanced student-teachers’ PCK and the factors influencing different PCK developmental trajectories were varied and personalized. Implications for teacher education are also discussed.